Multi-frequency, megawatt-power gyrotron to facilitate a wide range of operations at ITER - Ryosuke Ikeda; Takahiro Shinya; Satoru Yajima; Taku Nakai; Takeru Ohgo; Masayuki Tsuneyama; Hibiki Yamazaki; Takayuki Kobayashi; Ken Kajiwara (Nuclear Fusion, 2023)
High-power (1 MW), long-pulse operations up to 300 s were demonstrated by multi-frequency oscillations at 170 GHz, 137 GHz, and 104 GHz. A multi-frequency gyrotron based on the design of the ITER gyrotron has been developed and studied. By redesigning the built-in mode convertor and internal mirrors of the ITER gyrotron, the internal scattered power of the gyrotron was reduced while maintaining the same output beam size and beam direction for the three frequencies. In addition, the mirrors of a matching optics unit were designed to efficiently couple the RF beam at 170 GHz, 137 GHz, and 104 GHz oscillations to a waveguide 50 mm in diameter, the same size that will be used in ITER. An HE _11 mode content of ∼94% was achieved for the three frequencies. Output powers of 1 MW at 170 GHz and 137 GHz, and 0.9 MW at 104 GHz were demonstrated up to 300 s. These oscillation frequencies can facilitate in a wide range of toroidal magnetic field operations at ITER, including plasma start-up and electron heating and current drive.